Studies on Postnatal Development of Testis of Guinea Pig (Cavia porcellus) - Rajathi, S.; Ramesh, Geetha; Kannan, T. A.; Raja, K. (International Journal of Bio-resource and Stress Management, 2021)
The histology and histochemistry of the testis of guinea pig of various postnatal age groups was conducted. A total of 24 guinea pigs of four different postnatal ages with six male animals each were collected from the Department of Laboratory Animal Medicine, Madhavaram Milk Colony, Chennai as per the Ethical committee approval. After collection, animals were euthanized as per CPCSEA norms and testis was dissected out and was cut into small pieces, fixed and processed for paraffin embedding. Sections of 4–5 µm thickness were cut and used for the routine and special histological and histochemical staining techniques. Testes wereencapsulated by tunica vaginalis and tunica albuginea. Septa from the capsule divided the testicular parenchyma into lobules. Each lobule consisted of seminiferous tubules which consisted of spermatogenic cells in stratified layers and sertoli cells. Pre-weaning and weaning group of guinea pigs seminiferous tubules showed wide lumen with only type 1 and type 2 spermatogonia and sertoli cells. Young and adult animals seminiferous tubules showed narrow lumen with type 1 and type 2 spermatogonia, primary spermatocytes in various stages of differentiation, secondary spermatocytes, spermatids (early and late) and sertoli cells. Sertoli cells were large oval shaped cells with lightly stained irregular shaped nucleus. Interstitial tissue contained leydig cells in all ages.Leydig cells appeared as varied in shape. In all the age groups studied, PAS activity was noticed in the capsule and basement membrane. The micrometrical parameters increased as age advanced in both right and left testis.